Research into fatty acid composition of probiotic consortiums with the inclusion of propionic acid bacteria - Krupytska, Larysa; Kaprelyants, Leonid; Trufkati, Liudmyla; Shpyrko, Tatyana (Eastern-European Journal of Enterprise Technologies, 2017)
We studied fatty acid composition of the bacterial leaven of bifidobacteria and propionic acid bacteria that were grown together, and in a monoculture on the lactose medium with the addition of soybean serum in the amount of 3 %. The polyunsaturated fatty acids cannot be synthesized de novo in the organism of mammals. For this reason, searching for the new sources of polyunsaturated fatty acids is a relevant problem of biotechnology. Microorganisms appear to be a promising raw material. They are capable of synthesizing and accumulating in the cells up to 70 % lipids, including free fatty acids. In the course of the accumulation of biomass of the examined strains it was revealed that the propionic acid bacteria enter symbiotic relations with bifidobacteria. In the consortium, density of the population of both types of microorganisms was larger than that in a monoculture. We employed the dynamic method of gas chromatography in experimental studies using a flame-ionization detector. The results obtained allowed us to establish that the bacterial leaven В.longum-Ya3 and P.shermanii-PS4 differed from other samples by the high content of unsaturated fatty acids. In this leaven, the amount of linoleic acid was the largest and made up 23.99 % of the total sum of fatty acids. The data received confirm the expediency of using the probiotic bacteria for constructing the effective biologically active additives that contain essential fatty acids.